Approaches of learning among medical undergraduates of Faculty of Medicine and Health Sciences, Universiti Putra Malaysia in 2016 - Zakaria, Nurul Mursyidah; Jasman Farok, Nur Asyiqin; Adam, Siti Khadijah; Amin Nordin, Syafinaz (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Challenge arises for medical undergraduates as the subject of medicine is intricate and extensive. Although students come from the same pool of excellent academic background, the medical undergraduates are still prone to failure in exams, resulting in them repeating the year of study or even having the thought of changing to other courses. In order to cope with the programme, students may adopt learning approaches that would help them to go through the programme. Therefore, it would be interesting to explore the learning approaches of medical students in Universiti Putra Malaysia. Methods: The purposes of this study were to determine the learning approach of medical undergraduates of Faculty of Medicine and Health Sciences, Universiti Putra Malaysia (FMHS, UPM) together with its associated factors, which were socio-demographic characteristics and learning environment. This research was a cross-sectional study where the sample size calculated was 554. Self-administered questionnaires were given to the respondents chosen by simple random sampling. The socio-demographic characteristics were analysed using descriptive statistics such as frequency and percentage. Chi-square test was used to analyse the association between the variables. Results: The response rate was 83% (460 respondents agreed to participate). The majority of the respondents were females (73.7%), Malay (67%), and in their clinical years of study (58.7%). Overall, most students preferred deep approach (DA) of learning (49.6%), followed by strategic approach (29.1%) and surface apathetic approach (21.3%) of learning. There were statistically significant associations between learning approach and gender (p=0.005), as well as between learning approach and year of study (p=0.037). Conclusion: Our study showed an association between learning approaches and year of study and gender. DA of learning was the preferred learning approach in medical students at FMHS, UPM. This approach of learning, where students learn to understand the subject matter, may result in students become effective learners. Their understanding about the subject matter will be applicable to their clinical practice in the future.